Dependence of Green’s function of an e-dichotomous differential equation with matrix projector in the space M on parameters - Teplinsky, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
In the space M of bounded numeric sequences, we consider dichotomonly differential equation with a matrix projector. We prove that Green’s function of this equation exists, and give the conditions, under which it is continuous and differentiable with respect to the parameters in the equation.